Applying the factor analytical approach towards aaker’s brand personality model from an Islamic perspective - Ahmed, Muhammad; Jan, Muhammad Tahir (Malaysian Institute of Management, 2015)
Given current technologies, marketers are employing several techniques to differentiate their brands from others due to intense competition and low switching cost. Brand personality is one is one such approach. Aaker’s brand personality model with its five dimensions (sincerity, excitement, competence, sophistication, and ruggedness) has been used extensively in the field of marketing. Despite considerable research on Aaker’s model, scholars have also criticised it based on issues such as generalisability across countries and cultures. Considering religion an important yet ignored element of culture, this paper highlights the criticism on Aaker’s model from which we propose an Islamic brand personality model that we empirically test using exploratory factor analysis (EFA). Six factors emerged during EFA with a cumulative variance of 67.389 per cent. As per the findings, three new dimensions (humbleness, cooperation, trustworthiness, and justice) appeared during the analysis along with few pre-existing factors such as sincerity, competence, and excitement. Interestingly, the new dimension of trustworthiness and justice resulted in the highest contribution in terms of reliability and percentage of variance i.e. 0.90 and 13.859, respectively. The Islamic brand personality model can be applied on Islamic brands/organisations in order to evaluate their brand personality which will ultimately help marketers position their brands effectively.